Organic amendments alter aggregate-scale microbial communities linked to carbon sequestration in Mollisols - Miao Zhang; Yansheng Li; Zhenhua Yu; Jinyuan Zhang; Xiaojing Hu; Haidong Gu; Caixian Tang; Judong Liu; Junjie Liu; Shaoqing Zhang; Guanghua Wang; Xiaobing Liu; et al. (Applied Soil Ecology, 2026)

Identification and expression analysis of BAG gene family under salt and cold stress in soybean - Ping Sun; Zihan Kong; Xin Liu; Tiansheng Liu; Lina Jiang; Shimeng Xu; Hongli He; Zhiyao Dong; Xingzheng Zhang (Euphytica, 2026)

A global-local multi-scale feature extraction network for fine-grained segmentation of cyanobacterial blooms and aquatic vegetation - Yunchang Mu; Junsheng Li; Huan Zhao; Xiaodi Zhu; Zeyan Zhang; Fangfang Zhang; Shenglei Wang (Journal of Oceanology and Limnology, 2026)

Luteolin ameliorates sympathetic stress-induced myocardial injury by inhibiting the VEGFA/VEGFR2 and PI3K/Akt/NF-kappaB signaling pathways - Sheng Li; Yanli Guo; Peiyao Yang; Yaming Liu; Xinzhi Li; Ketao Ma; Li Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biochar-mediated microbial community and functional shifts regulate soil organic carbon fractions, enhancing carbon accumulation and stabilization in a subtropical plantation soil - Ting Li; Hongzhi Yang; Yuxin Tan; Mengzhu Jiang; Dechao Wu; Xiaoyong Chen; Wensheng Liu; Yelin Zeng; Kuan Peng; Yonghong Wang; Chan Chen; Guangjun Wang; et al. (Applied Soil Ecology, 2026)

Diversity and plant growth-promoting activity of rhizospheric and endospheric microbiomes from Cyperus rotundus L. in sugarcane fields of Guangxi, China - Haili Huang; Tao Zheng; Jingbo Li; Weisheng Li; Wei Zheng; Yonglin Ma; Meisha Qiu; Wenwei Tang; Yanhui Wang (Applied Soil Ecology, 2026)

Corrigendum to “Off-season wind-induced soil erosion from potato fields under varying bedding preparations”. [Aeolian Res. 74 (2025) 101000] - Matt Ball; Guillermo Hernandez-Ramirez; Willemijn Appels; Sheng Li; Rezvan Karimi Dehkordi (Aeolian Research, 2025)

Spatiotemporal dynamics and evolution of wind-sand along the Jiangjunmiao-Naomaohu Railway: Insights into patterns of wind-sand hazards based on a two-year field monitoring and mitigation exploration - Yupeng Shen; Lin Wang; Jamlick Kariuki; Xuedong Zhang; Zhisheng Liu; Yunxi Han; Dongtao Zhang; Shunyuan Zhong (Aeolian Research, 2025)

Off-season wind-induced soil erosion from potato fields under varying bedding preparations - Matt Ball; Guillermo Hernandez-Ramirez; Rezvan Karimi Dehkordi; Willemijn Appels; Sheng Li (Aeolian Research, 2025)

Amplification effects of AM fungus and rhizobacteria on carbon efficiency in wheat-soil system under drought stress via priming rhizosphere activities - Muhammad Maqsood Ur Rehman; Ling Zhao; Sidra Khattak; Yun-Li Xiao; Awais Iqbal; Wasim Khan; Muhammad Abrar; Zheng-Guo Cheng; Shi-Sheng Li; Asfa Batool; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Contrasting effects of litter and root removals on soil N2O emissions of an evergreen broadleaved forest in southeastern China - Lei Zhang; Weisheng Lin; Jordi Sardans; Enlan Xu; Dafeng Hui; Xiaofei Liu; Jinsong Wang; Shidong Chen; Jianfen Guo; Josep Peñuelas; Yusheng Yang (Applied Soil Ecology, 2025)

Meadow degradation reduces microbial β diversity and network complexity while enhancing network stability - Yuping Wu; Ansheng Liang; Mingjun Ding; Hua Zhang; Huan Xu; Yueju Zhang (Applied Soil Ecology, 2024)

Understory ferns removal downregulates microbial carbon use efficiency and carbon accrual in previously degraded lands - Cui Deng; Maokui Lyu; Xiaoling Xiong; Josep Peñuelas; Jordi Sardans; Xiaojie Li; Weisheng Lin; Yusheng Yang; Jinsheng Xie (Agricultural and Forest Meteorology, 2023)

Models overestimate ecosystem water use efficiency for northern permafrost regions - Jian Wang; Desheng Liu (Agricultural and Forest Meteorology, 2023)

Climate-smart management for increasing crop yield and reducing greenhouse gas emission in Beijing-Tianjin-Hebei region, China - Junfang Zhao; Hongfei Xie; Dongsheng Liu; Ruixi Huang; Huiwen Peng (Agricultural and Forest Meteorology, 2023)

A review on the pathogenic bacterium Nocardia seriolae : aetiology, pathogenesis, diagnosis and vaccine development - Yansheng Liu; Guoquan Chen; Liqun Xia; Yishan Lu (Reviews in Aquaculture, 2023)
Nocardia seriolae , a gram‐positive branching filamentous bacterium, is the causative agent of fish nocardiosis. It mainly infects fish through gills, anus, lateral line or surface injury, resulting in a large number of white nodules in visceral organs and skin ulcerations. N. seriolae can infect about 42 species of fish and severely harm the aquaculture industry in many regions, particularly in Asia. Aiming to have a more comprehensive understanding about N. seriolae , the literature of N. seriolae before January 2022 was collected by searching nine databases and the current knowledge of the host diversity, drug resistance, genotype and phenotype, virulence factor, molecular detection and vaccine development of N. seriolae was summarized in this review. The future studies of N. seriolae are also prospected in order to help the research on the pathogenic mechanism and control of N. seriolae infection .

A large-scale breeding experiment and observations on development of Cyanea nozakii (Scyphozoa, Cyaneidae) from fertilized eggs to larval medusae - Chun-sheng Liu; Zhi-meng Zhuang; Si-qing Chen; Jing-ping Yan; Chang-lin Liu; Jian-ming Sun (Hydrobiologia, 2015)

Potential of utilizing jellyfish as food in culturing Pampus argenteus juveniles - Chun-sheng Liu; Si-qing Chen; Zhi-meng Zhuang; Jing-ping Yan; Chang-lin Liu; He-tong Cui (Hydrobiologia, 2015)